ADVOCACY GROUPS FOR INDONESIAN WOMEN MIGRANT WORKERS PROTECTION - Aswatini Raharto; Mita Noveria (Jurnal Kependudukan Indonesia, 2012)
International labour migration is one possible means by which the Indonesian government could overcome the problems of providing employment for its economically active growing population, especially in the local contexts. However, due to low educational levels, lack of skills and tight competition with labour migrants from other countries, the majority of Indonesian migrant workers abroad can only partake in unskilled employment in the plantation, construction, domestic or other service sectors. In 2012, it was estimated that there were more than 6 million Indonesian migrant workers overseas, with between 30 to 40 per cent of the total number, women, mostly working as low-skilled labour in the service sector as domestic workers and care givers. It has become evident that Indonesian migrant workers are vulnerable to abusive behaviour and exploitation, since they 2 | Jurnal Kependudukan Indonesia lack protection of their basic human rights and their rights at work, with Indonesian women migrant workers, due to the nature of their work and gender discrimination, facing a higher risk of being exploited. The Indonesian government does not provide its citizens, working as labour migrants abroad, with enough of the safeguards advocated in international protective instruments. Indonesia ratified the International Convention on the Protection of the Rights of All Migrants Workers and Their Families (ICRMW) only on 12 April 2012 and this needs to be followed up by some government regulations for full implementation. This condition highlights the importance of increasing the attention of institutions (government and private) involved in managing Indonesian international labour migration, especially its female labour migration, to improve the protection of their rights. This paper elaborates the role and strategy of various advocacy groups, (e.g, Non Government Organizations) in empowering Indonesian women migrants/potential migrants regarding their rights and obligations; to ensure their legal protection. The information is from some qualitative studies involving relevant sources of information, conducted by the authors, especially in the Indramayu District, West Java and the Tulungagung District, East Java. The analysis is that based on a life-cycle approach to protect migrant rights during their pre deployment, their onsite protection (in destination/host countries), their return and their reintegration in their home countries.Keywords: Protection for Indonesian migrant workers, women migrant workers, advocacy, Non Government Organization